Burnout and coping mechanisms among healthcare professionals in central Uganda - Kabunga, Amir; Kigongo, Eustes; Okalo, Ponsiano; Udho, Samson; Grace, Anna Auma; Tumwesigye, Raymond; Akello, Anne Ruth; Musinguzi, Marvin; Acup, Walter; Nabaziwa, Jannat; Shikanga, Enos Mwirotsi; Namata, Haliama (Frontiers in Psychiatry, 2024)
Background The escalating global prevalence of burnout among healthcare professionals poses a serious health concern. Recent studies focus on prevalence and predictors of burnout among healthcare providers, emphasizing the need for well-being interventions. This study investigates burnout and coping mechanisms among healthcare professionals in central Uganda, addressing the dearth of knowledge about coping strategies specific to the region. Methods An analytical facility cross-sectional study was conducted in five healthcare facilities in central Uganda between June to July 2023. Participants included physicians, nurses, and technicians actively engaged in direct patient care. Data were collected using socio-demographic surveys, the Professional Quality of Life (ProQOL-5), and the Brief-COPE tools. Results The study revealed a high prevalence of burnout, with 39.8% of participants experiencing significant levels. Active coping, positive reframing, and denial were negatively correlated with low burnout levels. Dysfunctional coping, specifically self-distraction and denial, showed positive correlations with average and high burnout levels. Emotion-focused coping mechanisms were not employed across burnout levels. Conclusions The results emphasize the demanding nature of healthcare roles in the region and highlight the need for comprehensive, context-specific interventions to address burnout globally. While some healthcare professionals utilized adaptive strategies such as seeking social support, engaging in self-care activities, and utilizing problem-solving skills, others resorted to maladaptive coping mechanisms such as substance use and avoidance behaviors. This dichotomy highlights the need for targeted interventions to promote adaptive coping strategies and mitigate the negative impact of maladaptive behaviors on individual well-being and patient care.